2011
DOI: 10.1093/jxb/err245
|View full text |Cite
|
Sign up to set email alerts
|

Lignin metabolism has a central role in the resistance of cotton to the wilt fungus Verticillium dahliae as revealed by RNA-Seq-dependent transcriptional analysis and histochemistry

Abstract: The incompatible pathosystem between resistant cotton (Gossypium barbadense cv. 7124) and Verticillium dahliae strain V991 was used to study the cotton transcriptome changes after pathogen inoculation by RNA-Seq. Of 32 774 genes detected by mapping the tags to assembly cotton contigs, 3442 defence-responsive genes were identified. Gene cluster analyses and functional assignments of differentially expressed genes indicated a significant transcriptional complexity. Quantitative real-time PCR (qPCR) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
382
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 413 publications
(418 citation statements)
references
References 61 publications
33
382
1
2
Order By: Relevance
“…[See online article for color version of this figure. ] potato (Solanum tuberosum; Zhou et al, 2006;Klosterman et al, 2009). Typical symptoms caused by V. dahliae include leaf necrosis, premature defoliation, altered flowering time, and severe growth stunting (Veronese et al, 2003;Fradin et al, 2009;Xu et al, 2011b). Recent studies have identified signaling pathways that play essential roles in cotton resistance to V. dahliae (Xu et al, 2011b;Gao et al, 2013;Zhang et al, 2013), but how plants orchestrate development under V. dahliae infection remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[See online article for color version of this figure. ] potato (Solanum tuberosum; Zhou et al, 2006;Klosterman et al, 2009). Typical symptoms caused by V. dahliae include leaf necrosis, premature defoliation, altered flowering time, and severe growth stunting (Veronese et al, 2003;Fradin et al, 2009;Xu et al, 2011b). Recent studies have identified signaling pathways that play essential roles in cotton resistance to V. dahliae (Xu et al, 2011b;Gao et al, 2013;Zhang et al, 2013), but how plants orchestrate development under V. dahliae infection remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Typical symptoms caused by V. dahliae include leaf necrosis, premature defoliation, altered flowering time, and severe growth stunting (Veronese et al, 2003;Fradin et al, 2009;Xu et al, 2011b). Recent studies have identified signaling pathways that play essential roles in cotton resistance to V. dahliae (Xu et al, 2011b;Gao et al, 2013;Zhang et al, 2013), but how plants orchestrate development under V. dahliae infection remains elusive. By mining genes that are expressed differentially in response to V. dahliae from the cotton '7124', the WRKY transcription factor gene GbWRKY1 was identified as putatively functioning in the phosphate starvation and resistance response (Xu et al, 2011a(Xu et al, , 2012b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Production of phytoalexins, including terpenoids, and phenylpropanoid substances, is induced quickly in cotton on infection by V. dahliae (18,19). Gossypol is one of the most important sesquiterpene phytoalexin, which exists specifically in cotton and plays a crucial role in the defense against the invasion of pathogens and insects (20).…”
mentioning
confidence: 99%